1897 Fla. Laws 59 - (:unkn) unknown (My University, 1897)
An Act to Punish the Improper Exhibition of Dangerous Weapons, chap. 4532, § 1: Prohibited brandishing any dirk, dirk-knife, sword, sword-cane, gun, pistol, or other deadly weapon in a rude, careless, angry, or threatening manner not in self defense. Violators shall be punished by imprisonment not exceeding three months, or by fine not exceeding one hundred dollar, or both.
Keywords: BRANDISHING